2012
DOI: 10.1002/j.0022-0337.2012.76.4.tb05275.x
|View full text |Cite
|
Sign up to set email alerts
|

Predoctoral Fixed Implant Patient Satisfaction Outcome and Challenges of a Clinical Implant Competency

Abstract: Treatment with ixed and removable partial dentures has been the traditional method of addressing the replacement of teeth competencies in dental education. However, by 2013 the Commission on Dental Accreditation (CODA) standards will mandate a competency in "replacement of teeth including ixed, removable, and dental implants." In 2005, New York University College of Dentistry implemented a comprehensive implant program for predoctoral dental students. One of the outcome assessments of this program was to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 19 publications
2
24
0
1
Order By: Relevance
“…Out of 132 participants who received dental implants, 66% were satisfied, 26% were partially satisfied and 8% were unsatisfied with the therapy. A similar result was observed in studies conducted by Moghadam et al 19 , and Al-Radha et al 20 , which showed 85-96% and 86% satisfaction raterespectively.…”
Section: Discussionsupporting
confidence: 89%
“…Out of 132 participants who received dental implants, 66% were satisfied, 26% were partially satisfied and 8% were unsatisfied with the therapy. A similar result was observed in studies conducted by Moghadam et al 19 , and Al-Radha et al 20 , which showed 85-96% and 86% satisfaction raterespectively.…”
Section: Discussionsupporting
confidence: 89%
“…Outcomes of single-tooth dental implants have been evaluated, but there is great variation in the collection and reporting methodology [ 11 , 12 ]. Via telephone interviews, Moghadam et al reported a range of 85–96% for patient satisfaction in aesthetics, comfort, and function for patients treated in a predoctoral implant program [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patient perception of their oral health care is a core issue in evaluating the quality of service provided by dental students, as well as assessing the impact it may have on patient QoL. Limited available literature exists on patient perceptions of dental implant therapy provided by predoctoral dental students, especially based on patients’ age and gender . The use of OHIP‐49 has been validated and used; however, some research settings do not allow the use of the full OHIP‐49 .…”
mentioning
confidence: 99%